PENGARUH LAYANAN DIGITAL, LOKASI DAN DURASI LAYANAN TERHADAP KEPUASAN KONSUMEN MELALUI MINAT KONSUMEN SEBAGAI VARIABEL INTERVENING - Nuri Ervanto; Musran Munizu; Wardhani Hakim (Paulus Journal of Accounting (PJA), 2023)
Consumer problems when facing damage to Honda vehicles will look for information where, where, and tool solutions related to damage along with prices and processing time and how to make maintenance more effective and efficient. The purpose of this study is to improve the quality of service to customer satisfaction companies namely PT. Honda Sanggar Laut Selatan for consumer interest. The research method used is the Service Quality (Servqual) and Importance Performance Analysis (IPA) methods to measure the level of satisfaction and interest of a given consumer. Based on the results of the study indicate that the service quality of PT. Honda Sanggar Laut Selatan is quite good, but there is one service quality attribute that still needs to be improved or redeveloped from several service quality attributes, namely regarding digital services in providing solutions. Recommendations for improvements given include holding an introduction to the duration of the service, the good location is always published regularly. To measure the resulting digital services, testing was carried out using a questionnaire and several sample questions in the form of interactive media applications (Software SmartPLS version 3.0). The test results will show how much consumer interest in consumer satisfaction.